Efek Bantuan Sosial Dalam Membantu Kemakmuran Masyarakat Kurang Mampu Pada Desa Ulak Rengas Kecamatan Abung Tinggi Lampung Utara - riani, novi; Anwar L Nata, andrian (Margin: Jurnal Bisnis Islam dan Perbankan Syariah, 2024)
The government provides social assistance programs to the poor to help achieve community welfare programs by providing social assistance to the poor. The research used is descriptive research. Technical analysis of the data obtained was carried out using three types of triangulation through data reduction, data presentation, verification and confirmation of conclusions, then data validity, namely source triangulation. The effect of social assistance on the welfare of underprivileged communities in Ulak Rengas Village, Abung Tinggi District, North Lampung has positive and negative effects. Effect can be defined as a result or outcome. The social assistance provided and distributed by the Indonesian government to the poor is very diverse and varies, ranging from social assistance in the form of basic needs to financial assistance. The positive effects of income assistance can improve the economy of poor people, ease the burden of meeting living needs and help poor people manage and make maximum use of the results of life assistance to improve people's living standards. The negative effect of social assistance is that people feel dependent on social assistance, feel that their lives are being helped, people only depend on ordinary social assistance which causes a lack of public awareness of being satisfied, social assistance and improving the economy.